Development of a thiophene derivative modified LDH coating for Mg alloy corrosion protection. (10th January 2020) - Li, Lin-Xin; Xie, Zhi-Hui; Fernandez, Carlos; Wu, Liang; Cheng, Daojian; Jiang, Xiao-Hui; Zhong, Chuan-Jian
Abstract: A new thiophene derivative corrosion inhibitor (CI) was developed to functionalize the layered double hydroxide (LDH) primer on Mg alloy to enhance corrosion protection. Compared with bare LDH coating, the composite coatings consisting of a MgAl-LDH primer and an outer CI layer showed highly compact surface structures without large pores and gaps, thereby indicating the enhanced capability to resist the penetration of corrosive species. Electrochemical tests revealed that the MgAl-LDH film modified with the newly synthesized CI exhibited higher charge transfer resistance and lower corrosion current density than films modified with commercial CIs. The highest enhancement in corrosion resistance was linked to the film's ability to repair physical damage by forming precipitates through chemical complexation and adsorption of the CIs. These findings open up new opportunities for the design and synthesis of a thiophene-contained inhibitor to modify LDH films and to obtain a composite coating with superior corrosion protection. Graphical abstract: Image 1 Highlights: Intelligent anticorrosion coatings consist of LDH and inhibitor layers were obtained. As-synthesized NTA inhibitor can effective boost corrosion protection of LDH film. Anticorrosion properties of several inhibitor-treated LDH coatings are given. Adsorption structure of NTA molecule on the Mg (0001) surface was optimized.